Strategic brand design : designing brand identity from a marketing perspective - Stavorinus, Roel (Abingdon, Oxon ; New York, NY Routledge, 2025)
Translated from its original Dutch , Strategic Brand Design offers students and professionals a clear overview of the most important steps in developing brand identity from a marketing perspective. It aims to bridge the gap between marketer and designer, by containing all the knowledge that both parties need to understand and work together successfully on branding projects. Consisting of four parts, the book begins with a clear explanation of the most important marketing concepts in part 1, followed by a clear step-by-step plan for research and strategy in part 2. Part 3 provides a comprehensive toolkit for brand design based upon that strategy , while part four contains a plethora of methods, tools, and models for practice, as well as questions and assignments to support classroom teaching. Practical, accessible, and firmly grounded in research and theory, this book is an ideal reference guide for higher vocational students, and students on modules and programs relating to the fields of brand, design, marketing, and communication"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Branding (Marketing).; Brand name products$1 (BDesign.s; Corporate image$1 (BDesign.s; Brand design